2018
DOI: 10.1002/jcph.1300
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran as a Treatment Option for Heparin‐Induced Thrombocytopenia

Abstract: Heparin‐induced thrombocytopenia (HIT) is a potentially serious adverse drug reaction that can result in lethal vascular thrombosis. Dabigatran is a direct thrombin inhibitor that might be useful in the management of HIT. This study evaluated the efficacy and safety of dabigatran in patients with HIT. We included 43 patients in the study who received dabigatran for the management of suspected HIT, based on 4Ts (thrombocytopenia, timing of platelet count drop, thrombosis or other sequelae, and other causes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…15 In addition, Nasiripour et al reported the data on 40 patients who had received dabigatran for the treatment of suspected HIT based on 4Ts scores. 20 The normalization of platelet counts occurred in the case of all patients except for 2 cases that were related to the underlying conditions. Researchers did not detect any bleeding events or significant thrombosis during the 12month follow-up period.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…15 In addition, Nasiripour et al reported the data on 40 patients who had received dabigatran for the treatment of suspected HIT based on 4Ts scores. 20 The normalization of platelet counts occurred in the case of all patients except for 2 cases that were related to the underlying conditions. Researchers did not detect any bleeding events or significant thrombosis during the 12month follow-up period.…”
Section: Discussionmentioning
confidence: 85%
“…7 In recent years the efficacy and safety of DOACs, counting the direct thrombin inhibitor (dabigatran) along with the direct factor Xa inhibitors (rivaroxaban, apixaban, and edoxaban), have been evaluated in the treatment of clinical pathological HIT. [14][15][16][17]20 Rivaroxaban, as a direct factor Xa inhibitor, may act as a therapeutic option for heparin-induced thrombocytopenia. Approved treatment options for HIT such as argatroban are used parenterally and require repetitive coagulation monitoring and dose adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient's clinical context can favor the development of this iatrogenic complication, called heparin-induced thrombocytopenia (HIT) without or with associated thrombosis (HITT). When this complication occurs, it requires an immediate management with the withdrawal of heparin and use of an alternative anticoagulant [7][8][9][10][11]. If incorrectly managed, it can rapidly cause severe burden and become life-threatening.…”
Section: Introductionmentioning
confidence: 99%